Breaking Barriers: The Rise of Balinese Women in Politics and the Challenges They Face - Pinatih, I Gusti Ayu Agung Dewi Sucitawathi; Marijan, Kacung; Rian Prayana, I Kadek (Universitas Muhammadiyah Ponorogo, 2024)
This research aims to examine the strategies used by female politicians in Bali to balance their political careers with their social and cultural roles in the family and society. In addition, this study will also analyze the factors that influence the development of Balinese women's political careers. The method used is descriptive qualitative research with data collection through interviews and documentary studies. Interview data was collected from Balinese women politicians who are running for legislative members (Caleg) in the 2024 legislative elections (Pileg) from the Indonesian Solidarity Party (PSI), as well as from academics experienced in gender studies. The results showed that time management strategies and effective communication approaches are solutions for Balinese women in their multi-tasking roles. In addition, Balinese women are expected to innovate creatively by using technology to facilitate the management of household and work affairs in line with the concept of work-family balance. There are three important factors that influence Balinese women's political careers: first, cultural factors related to the still dominant patriarchal culture; second, structural factors reflecting the lack of allocation of strategic positions for women; and third, institutional factors related to the weakness of existing regulations to protect women's interests in the political arena.